Neonatal and Maternal Complications of Placenta Praevia and Its Risk Factors in Tikur Anbessa Specialized and Gandhi Memorial Hospitals: Unmatched Case-Control Study - Ashete Adere; Abay Mulu; Fikremelekot Temesgen (Hindawi Limited, 2020)
Background. Placenta praevia is a disorder that happens during pregnancy when the placenta is abnormally placed in the lower uterine segment, which at times covers the cervix. The incidence of placenta praevia is 3-5 per 1000 pregnancies worldwide and is still rising because of increasing caesarean section rates. Objective. To assess and identify the risk factors and maternal and neonatal complications associated with placenta praevia. Method and Materials. Target populations for this study were all women diagnosed with placenta praevia transvaginally or transabdominally either during the second and third trimesters of pregnancy or intraoperatively in Tikur Anbessa Specialized and Gandhi Memorial Hospitals. The study design was unmatched case-control study. Data was carefully extracted from medical records, reviewed, and analyzed. Unconditional logistic regression analysis was performed using adjusted odds ratios (AOR) with 95% confidence intervals. Results. Pregnancies complicated by placenta praevia were 303. Six neonatal deaths were recorded in this study. The magnitude of placenta praevia observed was 0.7%. Advanced maternal age (≥35) (AOR 6.3; 95% CI: 3.20, 12.51), multiparity (AOR 2.2; 95% CI: 1.46, 3.46), and previous history of caesarean section (AOR 2.7; 95% CI: 1.64, 4.58) had an increased odds of placenta praevia. Postpartum anemia (AOR 14.6; 95% CI: 6.48, 32.87) and blood transfusion 1-3 units (AOR 2.7; 95% CI: 1.10, 6.53) were major maternal complications associated with placenta praevia. Neonates born to women with placenta praevia were at increased risk of respiratory syndrome (AOR 4; 95% CI: 1.24, 13.85), IUGR (AOR 6.3; 95% CI: 1.79, 22.38), and preterm birth (AOR 8; 95% CI: 4.91, 12.90). Conclusion. Advanced maternal age, multiparity, and previous histories of caesarean section were significantly associated risk factors of placenta praevia. Adverse maternal outcomes associated with placenta praevia were postpartum anemia and the need for blood transfusion. Neonates born from placenta praevia women were also at risk of being born preterm, intrauterine growth restriction, and respiratory distress syndrome.